The efficacy and safety of tacrolimus on top of glucocorticoids in the management of IIM-ILD: A retrospective and prospective study - Chen, Yuxue; Bai, Zhiqian; Zhang, Ziyun; Hu, Qiongjie; Zhong, Jixin; Dong, Lingli (Frontiers in Immunology, 2022)
Objective To examine the efficacy of tacrolimus on top of glucocorticoids (GCs) in the management of idiopathic inflammatory myopathies-associated interstitial lung disease (IIM-ILD) and further assess the therapeutic benefit and safety of low-dose pirfenidone followed above treatments. Methods The retrospective study comprised 250 patients with IIM-ILD hospitalized in Tongji Hospital from 2014 to 2020. Demographic data, survival outcomes, and recurrence rates over the 1-year follow-up period were retrospectively analyzed. These patients were divided into two groups based on treatment with tacrolimus alone or other conventional immunosuppressants. Endpoints were compared by adjusted Cox regression model using inverse probability of treatment weighting to minimize treatment bias and potential confounders. For the prospective study, IIM-ILD patients treated with tacrolimus alone or tacrolimus combined with low-dose pirfenidone were enrolled from 2018 to 2020. Clinical characteristics, survival outcomes and multifarious assessment scales were followed up at baseline, 3, 6 and 12 months. The primary endpoint was 12-month survival rate and the secondary endpoints included respiratory-related events, adverse events, exacerbation in HRCT findings and laboratory parameters during therapy courses, and changes in respiratory function. Results For the retrospective study, tacrolimus group (n=93) had a significantly higher survival rate (weighted HR=0.330, p=0.002) and a lower relapse rate (weighted HR=0.548, p=0.003) compared with patients treated with other types of immunosuppressant (n=157) after adjustment. The prospectively enrolled 34 IIM-ILD patients were treated with tacrolimus (n=12) or tacrolimus combined with low-dose pirfenidone (n=22). After 12 months of treatment with tacrolimus, patients in the prospective cohort showed significant improvements in cardio-pulmonary function, disease activity, muscle strength, and mental scale from baseline. Subgroup analysis indicated that patients with tacrolimus and pirfenidone combination therapy showed lower chest HRCT scores (p=0.021) and lower respiratory-related relapse rates than those in tacrolimus monotherapy group (log-rank p=0.0029). The incidence rate of drug-associated adverse events (AEs) was comparable between two groups and none of the patients discontinued the treatment due to severe AEs. Conclusion Tacrolimus is well-tolerated and effective in the treatment of IIM-ILD. Furthermore, low-dose pirfenidone add-on treatment seems result in favorable improvements in pulmonary involvements for IIM-ILD patients. Clinical Trial Registration http://www.chictr.org.cn, identifier ChiCTR2100043595.